ANALISIS PERBANDINGAN INDEKS PEFORMANCE AYAM BROILER KANDANG SEMI CLOSE HOUSE DAN KANDANG CLOSE HOUSE DI HERAWATI FARM KECAMATAN KUTASARI KABUPATEN PURBALINGGA (STUDI KASUS) - Fridarti, Fridarti; Murbo P, Fajar Panjalu; Hidayati, Sari Gando; syafrizal, Syafrizal; Dianti, devi; Nazaruddin, nazaruddin (STOCK Peternakan, 2023)
This study aims to determine the comparison of semi-closed house cages with close house cages at Herawati Farm which can obtain a large Performance Index in Broiler chicken farming with a comparison of maintenance for one period. The formulation of the problem of this research is how the comparison of the Performance Index of Broiler semi Close House cages with Close House Cages at Herawati Farm. The method in this study uses the Survey method, with data collection using Observation, Documentation and Interview techniques. The Performance Index (IP) obtained in the Broiler farming business at Herawati Farm during one maintenance period in semi Close House cages is better than Close House cages. Semi Close House cages with FCR 1.458, for ABW reached 1.96 and 2.56% depletion while the harvest age was 33.00. In Close House cages the FCR results were 1.508, ABW reached 1.91, with the number of deletions 4.44 and harvest age 33.05. These results are inversely proportional to the hypothesis that the Performance Index (IP) and the largest income are obtained in the Close House cage system. Broiler body weight in semi-closed house cages is higher than in close house cages. Semi Close House cages have an average harvest age of 33.00 days, with a lower FCR (Feed Convertion Ratio) than Close House cages, and a lower Depletion rate compared to Close House cages. However, the Broiler farming business in semi-closed house cages and close house cages at Herawati Farm has an IP that is included in the very good category.